Efficacious pitch angle control of variable-speed wind turbine using fuzzy based predictive controller. (February 2020) - Iqbal, Atif; Ying, Deng; Saleem, Adeel; Hayat, Muhammad Aftab; Mehmood, Kashif
Abstract: The Wind energy is more reliable and speedier growing, among the renewable energy resources, due to the world environment challenges as well as increasing demand for energy. The wind turbine system's stability is cumbersome due to the uneven distribution of wind. Centrifugal and gravitational loads on the blades of a wind turbine creates weariness, resultantly decreases the power output along with the life of the equipment. Therefore, the need for a pitch angle control that can reduce the loading effect in addition to provide maximal power output. This paper proposes the fuzzy based model-predictive controller of pitch angle control to minimize the loading effect on wind turbine by limiting power output and rotor speed to its rated value as well as to maximize the extracted power output as compared to other techniques. The fuzzy logic controller works very efficiently by encountering the system's non-linearity while model predictive controller helps the system to become more stable and efficient. The superiority of prescribed controller is verified by comparing it with PI controller. The proposed model has been tested in MATLAB/Simulink using a 3MW wind turbine system.